A kind of Mxene-polyaniline composite negative electrode material and its preparation method and application
By doping phytic acid modified polyaniline into MXene material to form Mxene-polyaniline composite material, the structural stability and specific capacitance problems of MXene material in lithium-ion batteries are solved, and higher reversible specific capacity and cyclic stability are achieved.
Patent Information
- Application Number
- CN202210781674.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-04
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2042-07-04
AI Technical Summary
In the application of existing MXene materials in lithium-ion batteries, there are problems such as poor structural stability, low specific capacitance and short cycle life.
The phytic acid-doped polyaniline material is loaded between the layers or surfaces of the MXene material by co-precipitation method to form a Mxene-polyaniline composite material, thereby improving the specific surface area and spatial structure of the material.
The reversible specific capacity and cyclic stability of Mxene materials are improved, and the intercalation and removal rate of electrolyte ions between the material layers is enhanced.
Smart Images

Figure CN115101718B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of negative electrode materials, and specifically relates to a Mxene-polyaniline composite negative electrode material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have attracted a lot of attention due to their advantages such as high voltage, high energy density, long life and high safety. As a common negative electrode material for lithium batteries, MXene has been developed and applied to a certain extent in the field of energy storage.
[0003] In the prior art, a chemical liquid phase method is often used to etch MXene materials, thereby obtaining a stacked multi-layer structure of MXene materials. Then, dimethyl sulfoxide solvent is used as an intercalating agent to further ultrasonically treat the MXene material to obtain a few-layer or single-layer sheet structure. However, the intercalation ability of a single intercalating agent is limited, resulting in a low yield of this exfoliation method and the obtained single-layer structure is easy to stack again, that is, the stability is poor, which reduces the insertion and extraction rate of electrolyte ions between the layers of the MXene material, resulting in a low specific capacitance of the material.
[0004] CN109671949A discloses a MXene-based flexible composite negative electrode material. The specific process is to load transition metal sulfides on the two-dimensional layered structure of the MXene material through a hydrothermal method, thereby avoiding the agglomeration effect of the MXene material and the collapse of the layer structure, alleviating the volume expansion phenomenon of the transition metal polysulfide material during the charging process, and improving the cycle stability of the material. However, due to the poor stability of the sulfide, the cycle life of the assembled lithium-ion battery is short.
[0005] Therefore, in this field, there is an urgent need to develop a MXene-based negative electrode material that not only has good structural stability and high specific capacity, but also has good cycle stability. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a Mxene-polyaniline composite negative electrode material and its preparation method and application. The present invention uses a simple coprecipitation method to prepare a composite negative electrode material by doping polyaniline with phytic acid as a dispersant and Mxene material as a substrate, and uses the composite material in a lithium-ion battery, which not only improves the reversible specific capacity of a single material, but also improves the cycle stability of the material.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a Mxene-polyaniline composite negative electrode material, wherein the negative electrode material comprises a Mxene base material and a modified polyaniline material loaded in the Mxene base material;
[0009] The modified polyaniline material is a polyaniline material doped with phytic acid.
[0010] The present invention uses a chemical oxidation method to load the polyaniline material synthesized by doping phytic acid between the layers or on the surface of the MXene material to avoid stacking of the MXene material and agglomeration of the molecular chains of the polyaniline. The phytic acid contains 6 phosphate groups, which can interact with multiple amino groups in the polyaniline chain to form a three-dimensional network structure, and can also connect with the functional groups on the surface of the MXene material through hydrogen bonds, thereby promoting the insertion of polyaniline into the MXene material interlayer, thereby increasing the specific surface area and spatial structure of the material, and increasing the reversible specific capacity of a single material.
[0011] Preferably, the mass ratio of the Mxene base material and the modified polyaniline material in the Mxene-polyaniline composite negative electrode material is (2-5):1, for example, it can be 2:1, 2.2:1, 2.5:1, 2.8:1, 3:1, 3.2:1, 3.5:1, 3.8:1, 4:1, 4.2:1, 4.5:1, 4.8:1, 5:1.
[0012] In the present invention, by adjusting the mass ratio of the MXene substrate material and the modified polyaniline material, the capacitance and cycle stability of the composite material can be improved. A too low mass ratio will cause a large amount of modified polyaniline to agglomerate on the MXene surface, and the cycle stability of the composite material is not high due to the volume expansion effect of polyaniline as a pseudocapacitor material; on the contrary, a too high mass ratio will cause the effect of modified polyaniline to be small, and the capacity of the composite negative electrode material will not be significantly improved.
[0013] As a preferred technical solution of the present invention, the mass ratio of the Mxene base material to the modified polyaniline material in the Mxene-polyaniline composite negative electrode material is 3:1.
[0014] Preferably, the Mxene substrate material comprises Ti2CT x 、Ti3C2T x or Ti4C3T x Any one or a combination of at least two of x Selected from a hydroxyl group, a fluorine atom or a carbonyl group.
[0015] In a second aspect, the present invention provides a method for preparing the Mxene-polyaniline composite negative electrode material according to the first aspect, the method comprising the following steps:
[0016] (1) mixing aniline and phytic acid solution to form dispersion A, then adding phytic acid solution of ammonium persulfate for secondary mixing, filtering after reaction, and obtaining modified polyaniline material;
[0017] (2) mixing the Mxene material and solvent A to form a Mxene material solution, and then adding solvent B for secondary mixing, and obtaining the Mxene substrate material after centrifugation;
[0018] (3) The Mxene base material obtained in step (2) and the phytic acid solution are mixed to form a dispersion of the Mxene base material, and then the modified polyaniline material obtained in step (1) is added, mixed at low temperature to obtain a mixed solution, and then filtered to obtain the Mxene-polyaniline composite negative electrode material.
[0019] Preferably, the concentration of the phytic acid solution in step (1) is 0.05-0.09 mol / L, preferably 0.07 mol / L, for example, 0.05 mol / L, 0.06 mol / L, 0.07 mol / L, 0.08 mol / L, 0.09 mol / L. For the sake of brevity, the point values within the above range are no longer listed one by one.
[0020] In the present invention, by adjusting the concentration of the phytic acid solution, the phosphate carried by the phytic acid is conducive to the interaction with the amino groups on the multiple polyaniline chains to form a three-dimensional network structure, and can also promote the insertion of polyaniline into the MXene interlayer through hydrogen bonding with the functional groups on the surface of MXene, thereby increasing the specific surface area and spatial structure of the material and the reversible specific capacity of the single material. If the concentration of phytic acid is too low, the role of the phosphate cannot be exerted, and the conductivity of the synthesized polyaniline is low; on the contrary, if the concentration of phytic acid is too high, the fluidity of the mixed glue is low, and the prepared polyaniline is easy to agglomerate, which is also not conducive to the mixing of MXene and polyaniline, resulting in the inability of polyaniline to be loaded between the MXene layers or on the surface.
[0021] Preferably, the mixing temperature in step (1) is -2 to 2°C, for example, -2°C, -1°C, 0°C, 1°C, or 2°C.
[0022] Preferably, the mixing in step (1) is performed under stirring.
[0023] Preferably, the mass concentration of the dispersion A in step (1) is 11-17 mg / mL, for example, 11 mg / mL, 12 mg / mL, 13 mg / mL, 14 mg / mL, 15 mg / mL, 16 mg / mL, or 17 mg / mL.
[0024] Preferably, the mass ratio of ammonium persulfate to aniline in step (1) is (2.8-3.1):1, preferably 2.94:1, for example, it can be 2.8:1, 2.82:1, 2.85:1, 2.88:1, 2.9:1, 2.92:1, 2.94:1, 2.95:1, 2.98:1, 3:1, 3.1:1. For the sake of brevity, the point values within the above range are no longer listed one by one.
[0025] In the present invention, by adjusting the mass ratio of ammonium persulfate to aniline, the yield of polyaniline is improved, and the conductivity of the synthesized polyaniline is also high. If the mass ratio of ammonium persulfate to aniline is too low, the ammonium persulfate as an oxidant will be consumed quickly, the reaction is incomplete, and the yield of polyaniline is low; on the contrary, if the mass ratio of the two is too high, the possibility of generating small molecular products is also increased, and the conductivity and yield of the synthesized polyaniline are both low.
[0026] Preferably, the reaction temperature in step (1) is -2 to 2°C, for example, -2°C, -1°C, 0°C, 1°C, or 2°C.
[0027] Preferably, the reaction time in step (1) is 4 to 7 hours, for example, 4 hours, 5 hours, 6 hours, or 7 hours.
[0028] Preferably, the filtration in step (1) further includes a vacuum drying process.
[0029] Preferably, the vacuum drying process lasts for 6-9 hours, for example, 6 hours, 7 hours, 8 hours, or 9 hours.
[0030] Preferably, the solvent A in step (2) comprises dimethyl sulfoxide.
[0031] Preferably, the mixing temperature in step (2) is 35-45°C, for example, 35°C, 38°C, 40°C, 42°C, or 45°C.
[0032] Preferably, the mixing time in step (2) is 20-30 hours, for example, 20 hours, 22 hours, 25 hours, 28 hours, or 30 hours.
[0033] Preferably, the mass concentration of the Mxene material solution in step (2) is 0.07-0.12 g / mL, for example, 0.07 g / mL, 0.08 g / mL, 0.09 g / mL, 0.1 g / mL, 0.11 g / mL, 0.12 g / mL. For the sake of brevity, the point values within the above range are no longer listed one by one.
[0034] Preferably, the solvent B in step (2) is deionized water.
[0035] Preferably, the secondary mixing in step (2) is treated under ultrasound.
[0036] Preferably, the centrifugation in step (2) further includes a washing treatment.
[0037] Preferably, the concentration of the phytic acid solution in step (3) is 0.05-0.09 mol / L, preferably 0.07 mol / L, for example, it can be 0.05 mol / L, 0.06 mol / L, 0.07 mol / L, 0.08 mol / L, 0.09 mol / L. For the sake of space brevity, the point values within the above range are no longer listed one by one.
[0038] Preferably, the mixing in step (3) is performed under ultrasound.
[0039] Preferably, the temperature of the low-temperature mixing in step (3) is -2 to 2°C, for example, -2°C, -1°C, 0°C, 1°C, or 2°C.
[0040] Preferably, the low-temperature mixing time in step (3) is 8-11 hours, for example, 8 hours, 9 hours, 10 hours, or 11 hours.
[0041] Preferably, the mass concentration of the mixed solution in step (3) is 11-17 mg / ml, for example, 11 mg / mL, 12 mg / mL, 13 mg / mL, 14 mg / mL, 15 mg / mL, 16 mg / mL, 17 mg / mL.
[0042] Preferably, in step (3), the mass ratio of the modified polyaniline material obtained in step (1) to the Mxene base material obtained in step (2) is 1:(2-5), preferably 1:3, for example, it can be 1:2, 1:2.2, 1:2.5, 1:2.8, 1:3, 1:3.2, 1:3.5, 1:3.8, 1:4, 1:4.2, 1:4.5, 1:4.8, 1:5.
[0043] Preferably, the filtration in step (3) also includes a vacuum drying process.
[0044] Preferably, the temperature of the vacuum drying process is 40-60°C, for example, 40°C, 45°C, 50°C, 55°C, or 60°C.
[0045] Preferably, the vacuum drying process lasts for 6-9 hours, for example, 6 hours, 7 hours, 8 hours, or 9 hours.
[0046] In a third aspect, the present invention provides a negative electrode sheet, comprising a negative electrode active material, a binder and a conductive agent, wherein the negative electrode active material comprises the Mxene-polyaniline composite negative electrode material according to the first aspect.
[0047] In a fourth aspect, the present invention provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the negative electrode sheet is the negative electrode sheet according to the third aspect.
[0048] Compared with the prior art, the present invention has the following beneficial effects:
[0049] The present invention uses a chemical oxidation method to load the polyaniline material synthesized by doping phytic acid between the layers or on the surface of the MXene material to avoid stacking of the MXene material and agglomeration of the molecular chains of the polyaniline. The phytic acid contains 6 phosphate groups, which can interact with multiple amino groups in the polyaniline chain to form a three-dimensional network structure, and can also connect with the functional groups on the surface of the MXene material through hydrogen bonds, thereby promoting the insertion of polyaniline into the MXene material interlayer, thereby increasing the specific surface area and spatial structure of the material, and increasing the reversible specific capacity of a single material. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 This is the SEM image of the Mxene-polyaniline composite negative electrode material provided in Example 1. DETAILED DESCRIPTION
[0051] The technical solution of the present invention is further described below by combining the accompanying drawings and specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0052] Example 1
[0053] This embodiment provides a Mxene-polyaniline composite negative electrode material, wherein the negative electrode material comprises Ti3C2T x Substrate materials and Ti3C2T x The modified polyaniline material in the substrate material is a polyaniline material doped with phytic acid. The Ti3C2T x The mass ratio of the base material to the polyaniline is 3:1.
[0054] The preparation method of the negative electrode material is as follows:
[0055] (1) Aniline and a phytic acid solution with a concentration of 0.07 mol / L were stirred under ice bath conditions to form a dispersion A (mass concentration of 15 mg / mL), and then an equal volume of a phytic acid solution containing ammonium persulfate (concentration of 0.07 mol / L) was added for secondary mixing, wherein the mass ratio of ammonium sulfate to aniline was 2.94:1, and after a polymerization reaction under ice bath conditions for 5 hours, a precipitate was collected by vacuum filtration and dried in a vacuum oven at 50° C. for 7 hours to obtain a modified polyaniline material;
[0056] (2) Ti3C2T x and dimethyl sulfoxide at 40 °C and stirred for 24 h to form a Ti3C2T x The material solution was then added with deionized water for ultrasonic treatment for 4 h, and the Ti3C2T x Base material;
[0057] (3) The Ti3C2T obtained in step (2) x The substrate material and phytic acid solution with a concentration of 0.07 mol / L were ultrasonically treated for 2 h to form Ti3C2T x The dispersion of the base material is then added with the modified polyaniline material obtained in step (1), and stirred at low temperature for 9 hours under ice bath conditions to obtain a mixed solution (mass concentration of 15 mg / mL), which is then vacuum filtered to collect the precipitate, and dried in a vacuum oven at 50° C. for 7 hours to obtain the Mxene-polyaniline composite negative electrode material.
[0058] Figure 1 This is a SEM image of the MXene-polyaniline composite negative electrode material provided in Example 1. MXene has an obvious layered structure, and the rod-shaped polyaniline is successfully inserted between the MXene layers, which expands the specific surface area of the composite material and is beneficial to improving the composite performance of the material.
[0059] Example 2
[0060] This embodiment provides a Mxene-polyaniline composite negative electrode material, wherein the negative electrode material comprises Ti3C2T x Substrate materials and Ti3C2T x The modified polyaniline material in the substrate material is a polyaniline material doped with phytic acid. The Ti3C2T x The mass ratio of the base material to the polyaniline is 2.5:1.
[0061] The preparation method of the negative electrode material is as follows:
[0062] (1) Aniline and a phytic acid solution with a concentration of 0.06 mol / L were stirred under ice bath conditions to form a dispersion A (mass concentration of 13 mg / mL), and then an equal volume of a phytic acid solution containing ammonium persulfate (concentration of 0.06 mol / L) was added for secondary mixing, wherein the mass ratio of ammonium sulfate to aniline was 2.85:1, and after a polymerization reaction under ice bath conditions for 6 hours, a precipitate was collected by vacuum filtration and dried in a vacuum oven at 50° C. for 7 hours to obtain a modified polyaniline material;
[0063] (2) Ti3C2T x The material and dimethyl sulfoxide were stirred at 38 °C for 28 h to form a Ti3C2T x The material solution was then added with deionized water for ultrasonic treatment for 4 h, and the Ti3C2T x Base material;
[0064] (3) The Ti3C2T obtained in step (2) x The substrate material and 0.06 mol / L phytic acid solution were ultrasonically treated for 2 h to form Ti3C2T x The dispersion of the base material is then added with the modified polyaniline material obtained in step (1), and stirred at low temperature for 10 hours under ice bath conditions to obtain a mixed solution (mass concentration of 13 mg / mL), which is then vacuum filtered to collect the precipitate, and dried in a vacuum oven at 50° C. for 7 hours to obtain the Mxene-polyaniline composite negative electrode material.
[0065] Example 3
[0066] This embodiment provides a Mxene-polyaniline composite negative electrode material, wherein the negative electrode material comprises Ti3C2T x Substrate materials and Ti3C2T x The modified polyaniline material in the substrate material is a polyaniline material doped with phytic acid. The Ti3C2T x The mass ratio of the base material to the polyaniline is 4:1.
[0067] The preparation method of the negative electrode material is as follows:
[0068] (1) Aniline and a phytic acid solution with a concentration of 0.08 mol / L were stirred under ice bath conditions to form a dispersion A (mass concentration of 16 mg / mL), and then an equal volume of a phytic acid solution containing ammonium persulfate (concentration of 0.08 mol / L) was added for secondary mixing, wherein the mass ratio of ammonium sulfate to aniline was 3:1, and after a polymerization reaction under ice bath conditions for 6 hours, a precipitate was collected by vacuum filtration and dried in a vacuum oven at 50°C for 7 hours to obtain a modified polyaniline material;
[0069] (2) Ti3C2T x The material and dimethyl sulfoxide were stirred at 42 °C for 22 h to form a Ti3C2T x The material solution was then added with deionized water for ultrasonic treatment for 4 h, and the Ti3C2T x Base material;
[0070] (3) The Ti3C2T obtained in step (2) x The substrate material and phytic acid solution with a concentration of 0.08 mol / L were ultrasonically treated for 2 h to form Ti3C2T x The dispersion of the base material is then added with the modified polyaniline material obtained in step (1), and stirred at low temperature for 10 hours under ice bath conditions to obtain a mixed solution (mass concentration of 16 mg / mL), which is then vacuum filtered to collect the precipitate, and dried in a vacuum oven at 50° C. for 7 hours to obtain the Mxene-polyaniline composite negative electrode material.
[0071] Example 4
[0072] This embodiment provides a Mxene-polyaniline composite negative electrode material, wherein the negative electrode material includes Ti2CT x Substrate materials and Ti2CT x The modified polyaniline material in the substrate material is a polyaniline material doped with phytic acid. The Ti2CT x The mass ratio of the substrate material to the polyaniline is 2:1.
[0073] The preparation method of the negative electrode material is as follows:
[0074] (1) Aniline and a phytic acid solution with a concentration of 0.05 mol / L were stirred under ice bath conditions to form a dispersion A (mass concentration of 11 mg / mL), and then an equal volume of a phytic acid solution containing ammonium persulfate (concentration of 0.05 mol / L) was added for secondary mixing, wherein the mass ratio of ammonium sulfate to aniline was 2.8:1, and after a polymerization reaction under ice bath conditions for 4 hours, a precipitate was collected by vacuum filtration and dried in a vacuum oven at 50° C. for 6 hours to obtain a modified polyaniline material;
[0075] (2) Ti2CT x The material and dimethyl sulfoxide were stirred at 35 °C for 30 h to form a Ti2CT with a concentration of 0.07 g / mL. x The material solution was then added with deionized water for ultrasonic treatment for 4 h, and the Ti2CT was obtained after centrifugation, washing and drying. x Base material;
[0076] (3) The Ti2CT obtained in step (2) x The substrate material and 0.05 mol / L phytic acid solution were ultrasonically treated for 2 h to form Ti2CT x The dispersion of the base material is then added with the modified polyaniline material obtained in step (1), and stirred at low temperature for 8 h under ice bath conditions to obtain a mixed solution (mass concentration of 11 mg / mL), which is then vacuum filtered to collect the precipitate, and dried in a vacuum oven at 40° C. for 9 h to obtain the Mxene-polyaniline composite negative electrode material.
[0077] Example 5
[0078] This embodiment provides a Mxene-polyaniline composite negative electrode material, wherein the negative electrode material includes Ti2CT x Substrate materials and Ti2CT x The modified polyaniline material in the substrate material is a polyaniline material doped with phytic acid. The Ti2CT x The mass ratio of the base material to the polyaniline is 5:1.
[0079] The preparation method of the negative electrode material is as follows:
[0080] (1) Aniline and a phytic acid solution with a concentration of 0.09 mol / L were stirred under ice bath conditions to form a dispersion A (mass concentration of 17 mg / mL), and then an equal volume of a phytic acid solution containing ammonium persulfate (concentration of 0.09 mol / L) was added for secondary mixing, wherein the mass ratio of ammonium sulfate to aniline was 3.1:1, and after a polymerization reaction under ice bath conditions for 7 hours, a precipitate was collected by vacuum filtration and dried in a vacuum oven at 50°C for 9 hours to obtain a modified polyaniline material;
[0081] (2) Ti2CT x The material and dimethyl sulfoxide were stirred at 45 °C for 20 h to form a Ti2CT with a concentration of 0.12 g / mL. x The material solution was then added with deionized water for ultrasonic treatment for 4 h, and the Ti2CT was obtained after centrifugation, washing and drying. x Base material;
[0082] (3) The Ti2CT obtained in step (2) x The substrate material and phytic acid solution with a concentration of 0.09 mol / L were ultrasonically treated for 2 h to form Ti2CT x The dispersion of the base material is then added with the modified polyaniline material obtained in step (1), and stirred at low temperature for 11 hours under ice bath conditions to obtain a mixed solution (mass concentration of 17 mg / mL), which is then vacuum filtered to collect the precipitate, and dried in a vacuum oven at 60° C. for 6 hours to obtain the Mxene-polyaniline composite negative electrode material.
[0083] Example 6
[0084] The difference between this embodiment and embodiment 1 is that the mass ratio of the Mxene base material and the polyaniline in the Mxene-polyaniline composite negative electrode material is 1:1, and the rest is the same as embodiment 1.
[0085] Example 7
[0086] The difference between this embodiment and embodiment 1 is that the mass ratio of the Mxene base material to the polyaniline in the Mxene-polyaniline composite negative electrode material is 8:1, and the rest is the same as embodiment 1.
[0087] Example 8
[0088] The difference between this embodiment and embodiment 1 is that the mass ratio of ammonium persulfate to aniline in step (1) is 1:1, and the rest is the same as embodiment 1.
[0089] Example 9
[0090] The difference between this embodiment and embodiment 1 is that the mass ratio of ammonium persulfate to aniline in step (1) is 6:1, and the rest is the same as embodiment 1.
[0091] Example 10
[0092] The difference between this embodiment and embodiment 1 is that the concentration of the phytic acid solution in step (1) is 0.02 mol / L, and the rest is the same as embodiment 1.
[0093] Embodiment 11
[0094] The difference between this embodiment and embodiment 1 is that the concentration of the phytic acid solution in step (1) is 0.2 mol / L, and the rest is the same as embodiment 1.
[0095] Example 12
[0096] The difference between this embodiment and embodiment 1 is that the mass concentration of the mixed solution in step (3) is 5 mg / mL, and the rest is the same as embodiment 1.
[0097] Embodiment 13
[0098] The difference between this embodiment and embodiment 1 is that the mass concentration of the mixed solution in step (3) is 25 mg / mL, and the rest is the same as embodiment 1.
[0099] Comparative Example 1
[0100] The difference between this comparative example and Example 1 is that only the operation of step (1) is performed, and the rest is the same as Example 1.
[0101] Comparative Example 2
[0102] The difference between this comparative example and Example 1 is that only the operation of step (2) is performed, and the rest is the same as Example 1.
[0103] Comparative Example 3
[0104] The difference between this comparative example and Example 1 is that the Mxene base material is replaced with a graphite material, and the rest is the same as Example 1.
[0105] Comparative Example 4
[0106] This comparative example provides a Mxene-polyaniline composite negative electrode material, but no phytic acid is added. The phytic acid is replaced by common hydrochloric acid of equal concentration. The rest is the same as Example 1.
[0107] Application Examples 1 to 13 and Comparative Application Examples 1 to 4
[0108] The Mxene-polyaniline composite negative electrode materials provided in Examples 1 to 13 and Comparative Examples 1 to 4 are used to prepare lithium metal half-cells, and the preparation method is as follows:
[0109] The obtained Mxene-polyaniline composite negative electrode material, conductive agent Super P, and binder PVDF were mixed in a mass ratio of 8:1:1, and then mixed with an appropriate amount of NMP solvent to prepare an electrode slurry, which was then evenly coated on a copper foil and then placed in a vacuum drying oven and dried at 100°C for 12 hours. A slicer was used to prepare a negative electrode sheet with a diameter of 12 mm, and a lithium half-cell was assembled with lithium metal and electrolyte in a vacuum glove box filled with argon.
[0110] Test conditions
[0111] The lithium metal half-cells provided in Application Examples 1 to 13 and Comparative Application Examples 1 to 4 were subjected to performance tests. The test method is as follows: the prepared lithium half-cells were placed in an electrochemical workstation and subjected to a 0.1C rate charge and discharge cycle test with a voltage range of 0.1-1.5V. The initial specific capacity of the battery and the specific capacity after 120 cycles were recorded. The specific capacity after 120 cycles was divided by the initial specific capacity to obtain the capacity retention rate. The test results are shown in Table 1:
[0112] Table 1
[0113]
[0114] As can be seen from Table 1, from the above Examples 1-7 and Comparative Examples 1-2, the present invention prepares a MXene / polyaniline composite material with a layered structure by compounding MXene and polyaniline, and polyaniline is loaded on the surface and between the layers of MXene. The two act synergistically to increase the spatial structure of the material and improve the reversible specific capacity and cycle stability of the material. Too high a polyaniline content will cause a large amount of polyaniline to agglomerate on the surface of MXene. Due to the volume expansion effect of polyaniline as a pseudocapacitor material, the cycle stability of the composite material is not high; if the polyaniline content is too low, the effect of polyaniline is small, and the capacity of the composite material is not significantly improved. Among them, the application of lithium-ion batteries pays more attention to its cycle stability; MXene materials have higher cycle stability but lower specific capacity due to their layered structure, that is, high capacity retention rate; polyaniline as a pseudocapacitor material has high capacity but low cycle stability; Examples 4 and 6 cause the mass proportion of polyaniline to be higher than that of Example 1, so Examples 4 and 6 have higher initial capacities.
[0115] By comparing Example 1 with Examples 8-9, it can be seen that if the mass ratio of ammonium persulfate to aniline is too low, the ammonium persulfate as an oxidant will be quickly consumed, the reaction will be incomplete, the conductivity of the polyaniline will decrease, and the specific capacity of the composite material will also decrease; on the contrary, if the mass ratio of the two is too high, the possibility of generating small molecule products will also increase, and the conductivity and yield of the synthesized polyaniline will be low.
[0116] By comparing Example 1 with Examples 10-11, it can be seen that too high or too low a concentration of phytic acid is not conducive to the synthesis of polyaniline, resulting in lower capacity and cycle stability of the composite material synthesized later.
[0117] By comparing Example 1 with Examples 12-13, it can be seen that too high or too low a concentration of the mixed solution is not conducive to the insertion of polyaniline into the MXene interlayer, and the two cannot be combined, resulting in the prepared synthetic material being mainly polyaniline, and MXene only being a conductive agent and unable to play its electrochemical role. Among them, the mixed solution provided in the preparation process of Examples 12-13 causes Mxene and polyaniline to be unable to be effectively combined, Mxene only acts as a conductive agent (its role is equivalent to Super P), and polyaniline plays a major role, so the capacity of the negative electrode material provided by Examples 12-13 is higher.
[0118] By comparing Example 1 and Comparative Example 3, it can be seen that because the MXene surface contains hydrophilic functional groups (-OH, -F, =O), the wettability of the prepared graphite / polyaniline composite material in the electrolyte is weaker than that of the MXene / polyaniline composite material, and its specific capacity and cycle stability are worse than those of the present invention.
[0119] By comparing Example 1 and Comparative Example 4, it can be seen that the phosphate carried by phytic acid interacts with the amino groups on multiple polyaniline chains to form a three-dimensional network structure, and can also connect with the functional groups on the surface of MXene through hydrogen bonds to promote the insertion of polyaniline into the MXene interlayer. Therefore, the specific capacity and cycle stability of the composite material prepared by hydrochloric acid are inferior to those of the present invention.
[0120] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A Mxene-polyaniline composite negative electrode material, characterized in that: The negative electrode material includes a Mxene base material and a modified polyaniline material loaded in the Mxene base material; The modified polyaniline material is a polyaniline material doped with phytic acid; The mass ratio of the Mxene base material to the modified polyaniline material is (2-5):1; The Mxene-polyaniline composite negative electrode material is prepared by the following method, which comprises the following steps: (1) Aniline and phytic acid solution are mixed to form a dispersion A, and then a phytic acid solution of ammonium persulfate is added for secondary mixing, and after the reaction, the mixture is filtered to obtain a modified polyaniline material; The concentration of the phytic acid solution is 0.05-0.09 mol / L; The mass ratio of ammonium persulfate to aniline is (2.8-3.1):1; (2) Mixing the Mxene material and solvent A to form a Mxene material solution, then adding solvent B for secondary mixing, and obtaining the Mxene substrate material after centrifugation; (3) The Mxene base material obtained in step (2) and the phytic acid solution are mixed to form a dispersion of the Mxene base material, and then the modified polyaniline material obtained in step (1) is added, mixed at low temperature to obtain a mixed solution, and then filtered to obtain the Mxene-polyaniline composite negative electrode material.
2. The Mxene-polyaniline composite negative electrode material according to claim 1, characterized in that: The mass ratio of the Mxene base material to the modified polyaniline material in the Mxene-polyaniline composite negative electrode material is 3:
1.
3. The Mxene-polyaniline composite negative electrode material according to claim 1, characterized in that: The Mxene substrate material includes Ti2CT x 、Ti3C2T x or Ti4C3T x Any one or a combination of at least two of x Selected from a hydroxyl group, a fluorine atom or a carbonyl group.
4. A method for preparing a negative electrode material of a Mxene-polyaniline composite according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: (1) Aniline and phytic acid solution are mixed to form a dispersion A, and then a phytic acid solution of ammonium persulfate is added for secondary mixing, and after the reaction, the mixture is filtered to obtain a modified polyaniline material; The concentration of the phytic acid solution is 0.05-0.09 mol / L; The mass ratio of ammonium persulfate to aniline is (2.8-3.1):1; (2) Mixing the Mxene material and solvent A to form a Mxene material solution, then adding solvent B for secondary mixing, and obtaining the Mxene substrate material after centrifugation; (3) mixing the MXene base material obtained in step (2) and the phytic acid solution to form a dispersion of the MXene base material, and then adding the modified polyaniline material obtained in step (1), mixing at low temperature to obtain a mixed solution, and then filtering the mixed solution to obtain the MXene-polyaniline composite negative electrode material; The mass ratio of the modified polyaniline material obtained in step (1) to the Mxene base material obtained in step (2) is 1:(2-5).
5. The method according to claim 4, characterized in that The concentration of the phytic acid solution in step (1) is 0.07 mol / L.
6. The method according to claim 4, characterized in that The mixing temperature in step (1) is -2~2°C.
7. The method according to claim 4, characterized in that The mixing in step (1) is carried out under stirring.
8. The method according to claim 4, characterized in that The mass concentration of the dispersion A in step (1) is 11-17 mg / mL.
9. The method according to claim 4, characterized in that The mass ratio of ammonium persulfate to aniline in step (1) is 2.94:
1.
10. The method according to claim 4, characterized in that The reaction temperature in step (1) is -2~2°C.
11. The method according to claim 4, characterized in that The reaction time in step (1) is 4 to 7 hours.
12. The method according to claim 4, characterized in that The filtration in step (1) also includes a vacuum drying process.
13. The method according to claim 12, characterized in that The vacuum drying process lasts for 6-9 hours.
14. The method according to claim 4, characterized in that The solvent A in step (2) includes dimethyl sulfoxide.
15. The method according to claim 4, characterized in that The mixing temperature in step (2) is 35-45°C.
16. The method according to claim 4, characterized in that The mixing time in step (2) is 20-30 hours.
17. The method according to claim 4, characterized in that The mass concentration of the Mxene material solution in step (2) is 0.07-0.12 g / mL.
18. The method according to claim 4, characterized in that The solvent B in step (2) is deionized water.
19. The method according to claim 4, characterized in that The secondary mixing in step (2) is treated under ultrasound.
20. The method according to claim 4, characterized in that The centrifugation in step (2) also includes a washing process.
21. The method according to claim 4, characterized in that The concentration of the phytic acid solution in step (3) is 0.05-0.09 mol / L.
22. The method according to claim 21, characterized in that The concentration of the phytic acid solution in step (3) is 0.07 mol / L.
23. The method according to claim 4, characterized in that The mixing in step (3) is performed under ultrasound.
24. The method according to claim 4, characterized in that The temperature of the low-temperature mixing in step (3) is -2~2°C.
25. The method according to claim 4, characterized in that The low temperature mixing time in step (3) is 8-11 hours.
26. The method according to claim 4, characterized in that The mass concentration of the mixed solution in step (3) is 11-17 mg / mL.
27. The method according to claim 4, characterized in that In step (3), the mass ratio of the modified polyaniline material obtained in step (1) to the Mxene base material obtained in step (2) is 1:
3.
28. The method according to claim 4, characterized in that The filtration in step (3) also includes a vacuum drying process.
29. The method according to claim 28, characterized in that The temperature of the vacuum drying process is 40-60°C.
30. The method according to claim 28, characterized in that The vacuum drying process lasts for 6-9 hours.
31. A negative electrode sheet, characterized in that: The negative electrode sheet comprises a negative electrode active material, a binder and a conductive agent, and the negative electrode active material comprises the Mxene-polyaniline composite negative electrode material according to any one of claims 1 to 3.
32. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, and the negative electrode sheet is the negative electrode sheet according to claim 31.
Citation Information
Patent Citations
MXene-based flexible composite negative electrode material and preparation method thereof
CN109671949A